Achieving Professional and Personal Goals At the Beginning of the Year 2023 - Neale Fong (ACHSM, 2023)
Welcome to the first issue of the College's Asia Pacific Journal of Health Management for 2023. I trust the year is treating you well and you are well on your way to achieving professional and personal goals set at the beginning of the year. The College is moving forward with a successful year, too. In March we held a hugely successful Health Leadership Conference in Melbourne with well over 200 attendees. The focus on the common issues of leadership, workforce concerns and health system sustainability as well as aged care leadership and management was appreciated by all who participated. These issues of Workforce and Sustainability will be explored in more detail at the ACHSM Asia-Pacific Health Leadership Congress to be held in Canberra, 11-13 October, 2023. Please put a hold on those dates in your diary and register for this Congress.....